Desafios de familiares envolvidos no processo de cuidar de dependentes químicos - Costa, Lorena de Farias Pimentel (2015)
The increased consumption of licit and illicit drugs has permeated the daily life of many Brazilian families, encouraging involvement by substance abuse, nowadays recognized as an important risk factor to health and the production of physical, biological and psychological nature of damage in the lives of users and family. The changes in the care scenario in mental health promoted the development of actions based on community strategies, with emphasis on psychosocial rehabilitation and social integration, with support and responsibility of family caregivers. In the process of caring families face adverse situations capable of causing damage to its structure and relational dynamics, especially by frequent exposure to violence, financial bankruptcy, emotional distress and deterioration of emotional ties. This research aimed to: Reveal the challenges experienced by family members involved in the care of drug addicts, in view of the importance of their participation as supporting this process; Describe the coping strategies used by family members to the follow up of its chemical dependent relative; Identify the types of support used by the family during the process of rehabilitation and social integration; Reveal the family expectations in relation to health services as a source of support for the rehabilitation and social integration of their relative. It is comprehensive interpretive and qualitative study was conducted in a CAPS ad of Campina Grande - PB with a sample of ten family caregivers. The empirical material was collected through semi-structured interviews, analyzed through content analysis based on enunciation. The research followed the ethical precepts of the Resolution 466/12 of the CNS under the approval of the Ethics Committee in CCS research - UFPB June 2014 (Protocol 0297/14 and CAAE: 31639114.3.0000.5188). From the analysis of the empirical material formed by groups like discussing the experience of family members in the care process, and the main challenges fighting for them, namely: relapse, violence, financial damage and involvement in crime, personal degradation and of affective ties. Identified himself still coping strategies often based on dialogue and thus the functionality of the families that have strong and effective support networks, from participation in community religious groups, self-help groups and CAPS family groups. This service proved to be, in the perception of family, very effective with regard to support for overcoming crisis and emotional exhaustion moments. It was also possible to realize a deficit in operating strategy in the network, which makes it impossible for relatives to receive support from other care devices. The study showed that care for addicts causes severe disorders in the lives of families, especially those related to the constant stress and on the situations of despair and anguish is necessary to build a work in educational basis network and emotional support to the family aimed at the re-establishment of family dynamics.